The Role and Importance of the Service Sector in Increasing Employment in Rural Areas - ogli, Usmonov Murodbek Dusmurot (Goodwood Publishing, 2026)
Purpose: This study examines the role of the service sector in increasing employment in rural Uzbekistan. It analyzes the growth dynamics, regional distribution, and structural composition of services to understand their impact on diversifying rural employment and promoting inclusive growth. Research Methodology: This study uses official statistical data from January to November of 2024 to November of 2025. It employs quantitative analysis to assess the sector's growth trends, regional differences, and the role of small businesses in employment generation. The focus is on labor-intensive? sectors and their potential to create jobs in rural areas. Results: The findings revealed that the service sector is expanding steadily, with significant growth in trade, transport, accommodation, and financial and information services. Small businesses also play a crucial role in job creation. However, there are significant regional disparities in access to services, highlighting the uneven economic opportunities across rural regions. Conclusions: The service sector is a key mechanism for rural employment diversification and inclusive growth in Uzbekistan. To maximize its potential, supportive policies that focus on rural entrepreneurship, infrastructure development, and access to finance are essential. Limitations: This study is based on official statistical data, which may not capture informal sector activities or emerging industries, potentially limiting the understanding of sector dynamics. Contributions: This study provides insights into the role of the service sector in rural employment and economic diversification and offers policy recommendations for improving inclusive growth and regional employment.